Motywacja i wpływ uprawiania jogi na stan zdrowia – badanie własne = Motivation and influence practicing yoga on health - own study - Gwis, Katarzyna; Olejniczak, Dominik; Skonieczna, Joanna (Journal of Education, Health and Sport, 2016)
Gwis Katarzyna, Olejniczak Dominik, Skonieczna Joanna. Motywacja i wpływ uprawiania jogi na stan zdrowia – badanie własne = Motivation and influence practicing yoga on health - own study. Journal of Education, Health and Sport. 2016;6(9):554-565. eISSN 2391-8306. DOI 1http://dx.doi.org/10.5281/zenodo.154759 http://ojs.ukw.edu.pl/index.php/johs/article/view/3881 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 21.09.2016. Motywacja i wpływ uprawiania jogi na stan zdrowia – badanie własne Motivation and influence practicing yoga on health - own study Katarzyna Gwis1, Dominik Olejniczak2, Joanna Skonieczna2 1 Absolwentka kierunku Zdrowie Publiczne Wydział Nauki o Zdrowiu Warszawski Uniwersytet Medyczny 2 Warszawski Uniwersytet Medyczny Zakład Zdrowia Publicznego ul. Banacha 1a, 02-097 Warszawa Słowa kluczowe: joga, zdrowie, zachowania zdrowotne Key words: yoga, health, health behavior Streszczenie Wprowadzenie i cel pracy: Joga to jedna z form aktywności ruchowej. Joga oddziałuje na ciało i na umysł, dzięki czemu w prosty sposób pomaga zachować zdrowie. Celem badania była ocena wpływu uczestnictwa w zajęciach jogi na zdrowie. Materiał i metoda: Grupę badaną stanowiło 50 osób uczęszczających na zajęcia jogi. Udział w ankiecie był dobrowolny i poufny. Zastosowano autorski kwestionariusz. Wyniki: W grupie badanych, aż 48 osób (96%) stwierdziło, że ćwiczenia jogi pozytywnie wpływają na kształtowanie nawyków ruchowych. Ponad połowa badanych - 26 osób (52%) stwierdziła, że uczęszczanie na zajęcia jogi sprawiło, że wzrosło ich zainteresowanie zdrowym odżywianiem. Ponad połowa badanych – 26 osób (52%) jako główną korzyść płynącą z ćwiczeń jogi wskazała wzrost sprawności fizycznej. Ponad połowa osób ankietowanych – 28 osób (56%) zaobserwowała, że od kiedy ćwiczy jogę stany chorobowe występują rzadziej. Wnioski: Analizując wyniki przeprowadzonego badania własnego oraz dyskusję można stwierdzić, iż w związku z udokumentowanym pozytywnym wpływem jogi na stan zdrowia warto jest propagować tą formę rekreacji ruchowej we wszystkich grupach wiekowych, poczynając od dzieci, a kończąc na osobach w podeszłym wieku. Abstract Introduction: Yoga is a form of physical activity. Yoga affects the body and the mind, making it an easy way to help maintain good health. The aim of this study was to evaluate the effect of participation in the yoga exercises on health. Material and Methods: The study covered 50 people attending yoga exercises. Participation in the survey was voluntary and confidential. The study was conducted using a questionnaire designed by the author. Results: In the group of respondents, 48 people (96%) said that the yoga exercises positively affect the development of motor habits. More than half of respondents - 26 people (52%) said that attending yoga classes increased their interest in healthy eating. More than half of respondents - 26 people (52%) as a major benefit of yoga showed an increase in physical fitness. More than half of surveyed - 28 people (56%) observed that since they practice yoga illness occur less frequently. Conclusion: analyzing the results of the study and the discussion can be stated that in connection with documented positive effects of yoga on health, it is worth promoting this form of recreation for all age groups, starting with children, and ending of the elderly people.